Performance Evaluation of 3-RRPaR Parallel Manipulator in Pick and place Operation - Anrinal Anrinal; Randa Randa; Asmara Yanto (Jurnal Teknik Mesin, 2025)
This study evaluates the performance of a 3-RRPaR parallel manipulator designed to perform pick-and-place operations. The manipulator consists of three actuators driven by stepper motors, which are controlled through a G-code interface using Universal G-Code Sende.. Motion commands are input via a computer, enabling the robot to follow predefined trajectories. During testing, the manipulator was programmed to move within a circular workspace with a radius of 100 mm on the X and Y axes. The actual movement reached only 98 mm, resulting in a positioning error of approximately 2 mm. The observed inaccuracies are primarily attributed to structural inconsistencies between the upper and lower frames, unequal lengths of the passive links, and the use of a non-permanent clutch mechanism. These findings highlight the importance of mechanical precision and structural symmetry in enhancing the accuracy of parallel manipulator systems.